2016
DOI: 10.1039/c6cy00630b
|View full text |Cite
|
Sign up to set email alerts
|

A substrate-binding-state mimic of H2O2-dependent cytochrome P450 produced by one-point mutagenesis and peroxygenation of non-native substrates

Abstract: H2O2-dependent cytochrome P450s that can catalyze monooxygenation of nonnative substrates were constructed by one-point mutagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 52 publications
4
84
0
Order By: Relevance
“…In summary, we have constructed a unique approach for generating P450BM3 peroxygenase activity through the use of exogenous DFSMs. Our system achieved the best peroxygenase activity for the epoxidation of styrene, sulfoxidation of thioanisole, and hydroxylation of ethylbenzene among those P450‐H 2 O 2 system reported to date . We believe that this system can be further improved by optimizing the structure of the DFSMs in combination with rational design of the enzyme.…”
Section: Figurementioning
confidence: 82%
See 1 more Smart Citation
“…In summary, we have constructed a unique approach for generating P450BM3 peroxygenase activity through the use of exogenous DFSMs. Our system achieved the best peroxygenase activity for the epoxidation of styrene, sulfoxidation of thioanisole, and hydroxylation of ethylbenzene among those P450‐H 2 O 2 system reported to date . We believe that this system can be further improved by optimizing the structure of the DFSMs in combination with rational design of the enzyme.…”
Section: Figurementioning
confidence: 82%
“…The enantiomeric excess of the ( R )‐enantiomer was further improved to 91 % for the combination of F87A‐T268V/Im‐C6‐Phe. To our knowledge, this represents the highest enantioselectivity of styrene epoxidation achieved by P450s . In addition, DFSMs with various acyl amino acid groups produced different effects on the change in enantioselectivity (Table , Figure S13).…”
Section: Figurementioning
confidence: 91%
“… 144 , 145 Recently, Watanabe et al found that the mutation of the highly conserved threonine (T268 in P450 BM3 , Figure 13 ) into glutamic acid substantially enhanced the peroxygenase activity of a number of P450s, including P450 BM3 , P450 cam , and CYP119. 146 The glutamic acid mutation is thought to mimic the role of the substrate carboxyl group in CYP152 for O–O bond activation.…”
Section: Key Intermediates Involved In O 2 Activatmentioning
confidence: 99%
“… 306 , 408 , 409 In several alkene oxidation reactions, a cationic intermediate, presumably generated via single electron transfer from alkyl radical to the ferryl center, was inferred from the formation of aldehydes, ketone, or heme N -alkylated side products. 17 , 92 , 146 , 410 , 411 The ketone or aldehyde products were generated via a 1,2-hydride shift, while heme N -alkylation products were likely to be formed via direct electrophilic attack of the carbocation from a pyrrole nitrogen of the porphyrin ligand. 412 Very recently, Hammer, Arnold, and co-workers have harnessed the side activity of P450s for aldehyde formation to develop the first olefin anti-Markovnikov oxygenase (aMOx) via directed evolution ( Figure 45 b).…”
Section: C–h Functionalization Reactions Mediated By Oxoiron(iv) Porpmentioning
confidence: 99%
“…The ee value was further improved (to 91 %) with the combination of F87A/T268V and Im‐C6‐Phe. This result represents the highest enantioselectivity observed for styrene epoxidation by P450s . The potentially important role of DFSMs in contributing to the generation of chirality suggests that the DFSM‐facilitated P450BM3–H 2 O 2 system holds promise in the development of an enantioselective approach for P450‐catalyzed styrene epoxidation.…”
Section: Dual‐functional Small Molecule Co‐catalysis (Dfsm)mentioning
confidence: 99%